DISABLED PERSON X JOB MARKET IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2019)
Objective: To investigate the reality found in the insertion of the Person with Disabilities in the job market of PhysicalEducation, after the academic formation. Methodology: The interviewees were surveyed through social media, a list of approvedin the last magisterial competitions to the city hall and indications of other professionals in the area. As a data collectioninstrument, a questionnaire was composed of eighteen questions, applied to eleven professionals, who signed the TCLE.Results: Regarding the feeling about the future, after graduating, it can be said that the graduates were divided into two groups:two were worried and worried about the prejudice they had experienced throughout their lives and nine that were optimisticbecause they saw it as "an accomplished dream", "overcoming many difficulties. Final Considerations: We sought to analyze thereality of a DCP, seeking insertion in the job market, after its academic formation. Life experiences, adaptation and overcoming ofdisability, support and encouragement in the family relationship, experiences and practices in academic formation, differentialtreatment or prejudice, work and graduation relationships, future career prospects, relationships with students and clients andtheir possible suggestions for improvement in academic training, legislation and working conditions. It is hoped that the theme willstimulate a more critical and participatory society to the needs of the DCP, in the area, fomenting positive changes in society andthe academic environment.
Keywords: Person with Disabilities; Physical Education; Job market